2000
DOI: 10.5014/ajot.54.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Draw-A-Man Test as a Personal Neglect Test

Abstract: The Draw-A-Man Test is a reliable and valid tool for discriminating clients with personal neglect from those without.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The same questionnaire is administered to patients (self-evaluation) and carers. 5 Goodenough, 1926 ; Chen-Sea, 2000 Draw-A-Man test Using a blank piece of paper and a pencil, patients are asked to draw an entire man figure. The total score is 10, one point is given to each of the following body parts: head, trunk, right arm, left arm, right hand, left hand, right leg, left leg, right foot, and left foot.…”
Section: Resultsmentioning
confidence: 99%
“…The same questionnaire is administered to patients (self-evaluation) and carers. 5 Goodenough, 1926 ; Chen-Sea, 2000 Draw-A-Man test Using a blank piece of paper and a pencil, patients are asked to draw an entire man figure. The total score is 10, one point is given to each of the following body parts: head, trunk, right arm, left arm, right hand, left hand, right leg, left leg, right foot, and left foot.…”
Section: Resultsmentioning
confidence: 99%
“…According to Heilman and Van Den Abel (1980), the right hemisphere is considered to be dominant in mediating attention; therefore, left side neglect resulting from a right hemisphere lesion is seen more frequently than right side neglect. The impairments of unilateral neglect and inattention also have been reported to negatively affect performance in ADL and have been found to be important predictors of functional ability (Carter et al, 1988;Chen-Sea, 2000;Chen-Sea et al, 1993;Denes et al, 1982;Kinsella et al, 1993;Kinsella & Ford, 1980;Kotila et al, 1986). The present results as well indicate that the A-ONE can detect unilateral body neglect at a statisti-cally significant level as an impairment limiting performance in several tasks in patients with right CVA.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on the correlation between neurobehavioral impairments and specific ADL skills (Carter, Oliveira, Duponte, & Lynch, 1988;Chen-Sea, 2000;Chen-Sea, Henderson, & Cermak, 1993;Denes, Semenza, Stoppa, & Lis, 1982;Kinsella & Ford, 1980;Kinsella, Olver, Ng, Packer, & Stark, 1993;Kotila, Niemi, & Laaksonen, 1986). All reported that persons with unilateral neglect or visual-spatial inattention remain more dependent in ADL tasks than persons without neglect or attention deficits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, extrapersonal neglect was determined by the RCWCT, which has been shown to be a sensitive indicator of extrapersonal neglect (Chen-Sea & Henderson, 1994). Personal neglect was determined by the Draw-A-Man Test that has been shown to be a reliable and valid tool for measuring personal neglect (Chen-Sea, 2000). However, its sensitivity needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the performance of 110 normal Chinese subjects on the Draw-A-Man Test (Chen-Sea, 2000) and of 120 normal Chinese subjects on the RCWCT (Chen-Sea, Cermak, et al, 1993;Chen-Sea, Henderson, et al, 1993) were used to categorize patients as demonstrating personal neglect or extrapersonal neglect and normal. Based on lateralization of body parts representation and uncrossed words, the patients were grouped as the following: Group A (n = 26), test results within normal range ( Figure 1); Group B (n = 7), extrapersonal neglect only ( Figure 2); Group C (n = 2), personal neglect only (Figure 3), and Group 0 (n = 11), both personal and extrapersonal neglect ( Figure 4).…”
Section: Subject Groupingmentioning
confidence: 99%